Utilization of Used Bleaching Clay in Pellet Fuel Production with Torrefied Oil Palm Fronds - Pensiri Romyen; Yutthapong Pianroj; Teerasak Punvichai; Seppo Karrila; Aujchariya Chotikhun; Saysunee Jumrat (BioResources, 2023)
Torrefaction oil palm fronds was studied as a renewable biomass resource for efficient and sustainable pellet fuel production. Employing microwave heating during torrefaction, the process optimized the conditions to enhance the fuel properties. At 300 °C for 40 minutes, the torrefied oil palm fronds exhibited a remarkable rise in net calorific value to 23 MJ/kg, accompanied by a substantial increase in fixed carbon content to 46%. These enhancements signify a significant boost in energy content and carbon richness, which is crucial for cleaner and greener energy solutions. Comparing pellet fuels derived from raw and torrefied biomass, a striking difference in calorific values was observed. While raw biomass pellets reached 12.24 MJ/kg, their torrefied counterparts achieved an impressive 18.40 MJ/kg. This undeniable advantage highlights the effectiveness of torrefaction in elevating energy output. To optimize the composition of the pellet fuel, an ideal mass proportion of torrefied oil palm fronds and used bleaching clay was identified as 70:30. This blend resulted in the highest recorded calorific value, further endorsing the viability of the approach. In conclusion, torrefaction at 300 °C for 40 minutes proved to be a potent technique for enhancing oil palm fronds as a valuable source of pellet fuel. These findings underscore its potential to revolutionize renewable energy production, promoting sustainability and mitigating environmental impact.